Differential adeno-associated virus mediated gene transfer to sensory neurons following intrathecal delivery by direct lumbar puncture - Kitto Kelley F; Podetz-Pedersen Kelly M; Riedl Maureen S; Belur Lalitha R; Schuster Daniel J; Vulchanova Lucy; Wilcox George L; McIvor R Scott; Fairbanks Carolyn A (SAGE Publishing, 2010)
Abstract Background Neuronal transduction by adeno-associated viral (AAV) vectors has been demonstrated in cortex, brainstem, cerebellum, and sensory ganglia. Intrathecal delivery of AAV serotypes that transduce neurons in dorsal root ganglia (DRG) and spinal cord offers substantial opportunities to 1) further study mechanisms underlying chronic pain, and 2) develop novel gene-based therapies for the treatment and management of chronic pain using a non-invasive delivery route with established safety margins. In this study we have compared expression patterns of AAV serotype 5 (AAV5)- and AAV serotype 8 (AAV8)-mediated gene transfer to sensory neurons following intrathecal delivery by direct lumbar puncture. Results Intravenous mannitol pre-treatment significantly enhanced transduction of primary sensory neurons after direct lumbar puncture injection of AAV5 (rAAV5-GFP) or AAV8 (rAAV8-GFP) carrying the green fluorescent protein (GFP) gene. The presence of GFP in DRG neurons was consistent with the following evidence for primary afferent origin of the majority of GFP-positive fibers in spinal cord: 1) GFP-positive axons were evident in both dorsal roots and dorsal columns; and 2) dorsal rhizotomy, which severs the primary afferent input to spinal cord, abolished the majority of GFP labeling in dorsal horn. We found that both rAAV5-GFP and rAAV8-GFP appear to preferentially target large-diameter DRG neurons, while excluding the isolectin-B4 (IB4) -binding population of small diameter neurons. In addition, a larger proportion of CGRP-positive cells was transduced by rAAV5-GFP, compared to rAAV8-GFP. Conclusions The present study demonstrates the feasibility of minimally invasive gene transfer to sensory neurons using direct lumbar puncture and provides evidence for differential targeting of subtypes of DRG neurons by AAV vectors.